GEOLOGIA E LITOQUÍMICA DE FRAGMENTO DO GREENSTONE BELT DE CRIXÁS (ARQUEANO-PALEOPROTEROZÓICO) NO ARCO MAGMATICO DE GOIÁS (NEOPROTEROZÓICO): REGIÃO REISÓPOLIS-UIRAPURÚ (GO). - Kuyumjian, Raul Minas; Ferreira Filho, Cesar Fonseca; Nakayoshi, Takato; Ferreira, Luiz Felipe Dias (Geochimica Brasiliensis, 2015)
The supracrustal rocks from the Uirapurú-Reisópolis region includeperidotitic komatiite, overlaid by garnet-quartz-chlorite schist, quartz-muscoviteschist, quartzite, garnet-rich quartzite, metagreywacke, metachert,amphibolite and banded iron formation. This sequence is intruded by granitesand gabbros. Supracrustal rocks are metamorphosed in the transitionfrom greenschist to epidote facies metamorphism. Hydrothermally alteredamphibolite and iron formation in the Bocaina shear zone are enriched inAu, As, Ag, Cu, Ba, Bi, Sb and W. Several exploration programs for goldand nickel were developed by mining companies in that region since the‘80s. The studied rocks occur in a region with gold, copper, nickel, barite,emerald and kyanite deposits.